Computation of the MLE of the Non-Centrality Parameter of the Non-Central X^2 Distribution - Shalabi, Bahlul Omar (The Libyan Journal of Science, 2015)
In this paper, a Matlab computer program is presented for finding the maximum likelihood estimate of the non-centrality parameter of the non-central chi squared distribution with  degrees of freedom.